Clear Aligner System and Its Role in Tooth Movements During Orthodontic Treatments: A Narrative Review - Ferial Msallam,; Salimah Himeer, (AlQalam Journal of Medical and Applied Sciences, 2025)
Since most patients, especially adults, don't like the way fixed appliances look, clear aligner therapy (CAT) has drawn interest from both patients and physicians. Clear aligners bring unique therapeutic issues due to their distinct material features, biomechanical properties, and treatment efficiency. The clear aligner was first introduced as the Invisalign® system in 1997 by Align Technology© (Santa Clara, CA) 1997 which was produced by computer-aided design and computer-aided manufacturing (CAD-CAM). Simple tooth movement was initially treated by the Invisalign technology. But as technology advanced, the manufacturer started utilizing intermaxillary elastics and attachments to achieve various tooth motions, making Invisalign a competitive substitute for fixed appliances. In order to ensure the clinical success of CAT, this narrative review examined the indications and contraindications of CAT, as well as its effectiveness and limits, the CAT concept, and movement mechanics provided by various attachment types, clinical procedures, follow-up, and complication issues. In summary, CAT has undergone improvement throughout the past several years. Patient adherence, case selection, and the clinician's personal experience all affect the outcome of therapy. It is recommended that the patient be informed of the benefits and drawbacks of CAT by the practitioner, and they should only take the device off when eating.